DYNAMICS OF COOPERATION AND COMPETITION STRATEGIES IN DETERMINING COMPANY PERFORMANCE AMIDST CHANGING LEVELS OF COMPETITION, MARKET DYNAMICS AND FLUCTUATING TECHNOLOGICAL CHANGES - Herry Achmad Buchory; Uce Karna Suganda; Zaenal Aripin (PT. Kreatif Indonesia Satu, 2024)
The dynamics of cooperative and competitive strategies play a key role in determining company performance amidst changes in the level of competition, market dynamics and fluctuating technological changes. In a dynamic business environment, companies often face challenges to remain competitive and achieve sustainable growth. Factors such as strategic fit with partners, trust, relative advantage, organizational factors, and external factors such as market conditions and regulations influence the success of cooperation strategies. Integrating cooperation strategies with competitive strategies is key to ensuring that cooperation supports the company's long-term business goals while maintaining a competitive advantage in the market. With a holistic and well-planned approach, companies can leverage cooperative strategies to increase their competitiveness and achieve sustainable growth in a rapidly changing business environment.